﻿A new subterranean species of Entomoculia Croissandeau, 1891 from the Canary Islands, Spain (Coleoptera, Staphylinidae, Leptotyphlinae) - Carles Hernando; Heriberto López (Contributions to Entomology)
The genus Entomoculia Croissandeau, 1891, is the only representative of the subfamily Leptotyphlinae present in the Canary Islands and is composed by only two species: E. (Stenotyphlus) canariensis Outerelo, 1982, from La Gomera and E. (Stenotyphlus) lauricola Outerelo & Hernández, 1989, from Tenerife, both found in deep soil (= endogean) habitats. In this paper, we describe Entomoculia (Stenotyphlus) vulcanica sp. nov., the third Canarian species of the genus, which is reported for the first time from Gran Canaria and has been found in the mesovoid shallow substratum “MSS”. This new species has some of the characteristics that are specific to Canarian species of the genus Entomoculia, such as the lack of a denticle or spiniform process on the male metatrochanters. However, it is a remarkable species as it is the only known species of the genus with a tridentate labrum, as the labrum is monodentate in the species so far known from Canary Islands and bidentate in non-Canary species. We provide a key to Canarian species and illustrations of the habitus and the primary and secondary sexual characters of the male. We also describe the sampling techniques used and provide detailed information on habitat characteristics and associated arthropod fauna.